Public Relations Strategies in Increasing the Interest of Prospective New Students: A Study at SMKN 1 Gunungkencana, Lebak Regency - Ali Nurdin; Siti Suiyah (MID Publisher International, 2023)
This study aims to analyze the public relations (PR) strategy in increasing prospective student interest at SMK Negeri 1 Gunungkencana. The research employed a qualitative approach within a constructivist paradigm. Data were collected through observation, in-depth interviews, and documentation. Research informants consisted of the Principal, Head of Public Relations, Head of the Accounting and Financial Institution Program, and Head of the Automotive Engineering Program. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the school's public relations strategy was implemented through four main stages: identifying opportunities and problems, program planning, communication implementation, and program evaluation. The strategies included strengthening the school image through the “SMK Kencana Kemilau” branding, conducting promotional visits to junior secondary schools, utilizing social media and the school website, developing entrepreneurship programs, and establishing partnerships with business and industrial sectors. The most attractive public relations program for prospective students was the Industrial Work Practice (Prakerin) program, as it provided real-world work experience and opportunities to obtain competency certificates from partner companies. The study also found that the school's primary opportunities included its strategic location, an accreditation status, and qualified human resources. Meanwhile, the major challenges were increasing competition among schools, limited public understanding of vocational education, and certain infrastructure constraints. This study concludes that a well-planned public relations strategy, supported by flagship programs and effective communication media, plays a significant role in building a positive school image and increasing prospective student enrollment interest.